Dampak Bullying terhadap Kepercayaan diri Siswa di Sekolah Dasar Negeri 002 Palembang - Rizky Febriyanto; Murjainah Murjainah; Yuliana Yuliana; Hasbillah Hasbillah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
This study aims to describe the effect of bullying on students' self-confidence at State Elementary School 002 Palembang using a descriptive method with a qualitative approach. Bullying in the school environment, whether in verbal, physical, or social forms, has the potential to negatively affect students’ psychological well-being, particularly their level of self-confidence. The subjects of this study consisted of students and teachers selected through purposive sampling techniques to ensure relevance to the research objectives. Data collection was carried out through observations, in-depth interviews, and documentation to obtain comprehensive and valid information. The data were then analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing to identify patterns and relationships. The findings reveal that students who experience bullying tend to have low self-confidence. This condition is reflected in their lack of courage to speak in front of others, a tendency to withdraw from social interactions, and hesitation in expressing opinions or participating in class activities. These impacts not only affect academic performance but also hinder students’ social development. Therefore, it is essential for schools to take preventive and responsive actions by creating a safe, supportive, and inclusive learning environment that fosters students’ confidence and emotional well-being.